The Paradox of Poverty: Exploring the Intersection of Online Loan Defaults and Corruption Among Low-Income Communities - Kurniawan, Reza; Triyadi, Rudini (Jogjakarta Communication Conference (JCC), 2025)
The rise of online lending platforms in Indonesia is accompanied by significant issues, one of which is the "galbay" (gagal bayar) movement that has emerged through Facebook groups advocating for individuals to default on their online loans. While the Technology Acceptance Model affirms the convenience of digital lending platforms, there exists a disjunction between culturally prescribed financial goals and the institutional means available to achieve them, leading to an anomie within the social structure. This paper employs netnography to explore the "Raja Galbay" group on Facebook, examining the motivations and behaviors of its members. this paper explore the motivation, causes, and how user decided to default their online lending. Concern like privacy, collective movement exploration also discussed in this paper.  indicate that online communities play a critical role in shaping the perception and behavior of individuals facing financial distress. This galbay movement is recognized as a legitimate reaction to financial difficulties rather than a violation of ethical or legal responsibilities. The community functions not only as a platform for sharing information but also as a support network that reinforces the normalization of loan defaults. These observations underscore the necessity for a more nuanced approach to financial regulation and consumer protection, taking into account the social dynamics that shape financial decision-making in digital environments.